Development of a multicopter-carried whole air sampling apparatus and its applications in environmental studies. (February 2016) - Chang, Chih-Chung; Wang, Jia-Lin; Chang, Chih-Yuan; Liang, Mao-Chang; Lin, Ming-Ren
Abstract: To advance the capabilities of probing chemical composition aloft, we designed a lightweight remote-controlled whole air sampling component (WASC) and integrated it into a multicopter drone with agile maneuverability to perform aerial whole air sampling. A field mission hovering over an exhaust shaft of a roadway tunnel to collect air samples was performed to demonstrate the applicability of the multicopter-carried WASC apparatus. Ten aerial air samples surrounding the shaft vent were collected by the multicopter-carried WASC. Additional five samples were collected manually inside the shaft for comparison. These samples were then analyzed in the laboratory for the chemical composition of 109 volatile organic compounds (VOCs), CH4, CO, CO2, or CO2 isotopologues. Most of the VOCs in the upwind samples (the least affected by shaft exhaust) were low in concentrations (5.9 ppbv for total 109 VOCs), posting a strong contrast to those in the shaft exhaust (235.8 ppbv for total 109 VOCs). By comparing the aerial samples with the in-shaft samples for chemical compositions, the influence of the shaft exhaust on the surrounding natural air was estimated. Through the aerial measurements, three major advantages of the multicopter-carried WASC were demonstrated: 1. The highly maneuverable multicopter-carried WASC can be readily deployed for three-dimensional environmental studies at a local scale (0−1.5 km); 2. Aerial sampling with superior sample integrity and preservation conditions can now be performed with ease; and 3. Data with spatial resolution for a large array of gaseous species with high precision can be easily obtained. Highlights: A sampling device was integrated with a multicopter drone to perform aerial sampling. The whole air sampling can be performed at desired positions aloft with ease. The leak- and contamination-free properties ensured the integrity of air samples. Subsequent in-lab analysis of whole air samples provided a large variety of species. Vertical profiles of gaseous species up to 1 km height can be easily obtained.